Environmental accidents and environmental legislation in China: Evidence from provincial panel data (1997–2014). Issue 1 (21st November 2021) - Zang, Xiaowei
Abstract: Knowledge on environmental disasters and legislation is limited. I narrow this knowledge gap by examining the relationship between environmental accidents and climate legislation in the People's Republic of China. I offer an account of local environmental accidents and local environmental legislation and focus on political centralization to understand bill submission and bill enactment in local climate legislation in China. I built a unique provincial panel dataset for the period of 1997–2014 ( N = 527) for the data analysis and found that environmental accidents are correlated with local climate legislation. I also discuss how local government leaders make rational choices under the incentive system in the Chinese bureaucracy in the wake of environmental accidents. Related Articles: Brogan, Michael James. 2017. "Evaluating Risk and Natural Gas Pipeline Safety." Politics & Policy 45(4): 657–80. https://doi.org/10.1111/polp.12211 Liu, Zezhao, and Zhengwei Zhu. 2021. "China's Pathway to Domestic Emergency Management: Unpacking the Characteristics in System Evolution." Politics & Policy 49(3): 619–50. https://doi.org/10.1111/polp.12407 Neill, Katharine A., and John C. Morris. 2012. "A Tangled Web of Principals and Agents: Examining the Deepwater Horizon Oil Spill through a Principal–Agent Lens." Politics & Policy 40(4): 629–56. https://doi.org/10.1111/j.1747‐1346.2012.00371.x Abstract : Accidentes ambientales y legislación ambiental en China: evidencia de datos de paneles provinciales (1997–2014): El conocimiento sobre desastres ambientales y legislación es limitado. Reduzco esta brecha de conocimiento examinando la relación entre los accidentes ambientales y la legislación climática en la República Popular China (RPC). Ofrezco un relato de los accidentes ambientales locales y la legislación ambiental local y me concentro en la centralización política para comprender la presentación de proyectos de ley y la promulgación de proyectos de ley en la legislación climática local en China. Construí un conjunto de datos de panel provincial único para el período 1997–2014 ( N = 527) para el análisis de datos y descubrí que los accidentes ambientales están correlacionados con la legislación climática local. Discuto cómo los líderes del gobierno local toman decisiones racionales bajo el sistema de incentivos en la burocracia china a raíz de accidentes ambientales. Abstract : 中国的环境事故和环境立法：省级面板数据得出的证据（1997–2014）: 关于环境灾害和环境立法的研究并不充足。我通过分析中华人民共和国（PRC）的环境事故和气候立法之间的关系，进而缩小了该知识差距。我描述了地方环境事故和地方环境立法，并聚焦于政治中心化，以期理解中国地方气候立法中的法案提交及颁布。我建立了一个独特的、针对1997–2014年的省级面板数据集（ N = 527）以用于数据分析，分析结果发现，环境事故与地方气候立法相联系。我探讨了中国官僚主义的激励系统下，地方政府领导者在环境事故发生后如何制定理性决策。